Experiences of violence while in insecure migration status: a qualitative evidence synthesis - Alexandria Innes; Annie Bunce; Hannah Manzur; Natalia V. Lewis (Globalization and Health)
Abstract Background The global movement of people in the context of strict immigration laws and policies places significant numbers of people in insecure migration status worldwide. Insecure status leaves people without recourse to legal, governmental or social protection from violence and abuse. This review synthesized qualitative studies that reported how migrants associated physical and physically enforced sexual violence they experienced with their insecure migration status. Methods We conducted a qualitative evidence synthesis of 31 studies published between 1 January 2000 and 31 May 2023, with data from Europe, North America, East Asia, South Asia, the Middle East and Africa. Our thematic synthesis produced 14 inductive descriptive codes, four descriptive themes and three analytical themes. Results We generated robust qualitative evidence showing that women experienced sexual violence while in transit or without status in a host state, and that they associated that violence with their insecure migration status. This was the case across the various geographic routes and destination countries. We found evidence that women associated intimate partner violence with lacking (legal) access to support because of their insecure migration status. We found evidence that women connected their unwillingness to leave violent circumstances, and therefore their prolonged or repeated exposure to violence, with a fear of immigration removal produced by their insecure migration status. Conclusion To protect people in insecure migration status from experiencing violence that they associated with their migration status, it’s necessary to ensure that the reporting of violence does not lead to immigration enforcement consequences for the victim.